Measuring Human-Animal Attachment in a Large U.S. Survey: Two Brief Measures for Children and Their Primary Caregivers - Bures, Regina M.; Mueller, Megan Kiely; Gee, Nancy R. (Frontiers in Public Health, 2019)
One challenge faced by researchers in the human-animal interaction (HAI) field is generalizing the impact of pet ownership and companion animal interaction to larger populations. While researchers in Europe and Australia have included measures of pet ownership and attachment in surveys (e.g., the Avon Longitudinal Study of Parents and Children) for some time, survey researchers in the United States have been slow to incorporate questions related to HAI in population representative studies. One reason for this may be that many of the current HAI-related measures involve long, complex scales. From the survey administration perspective, using complex scales is costly in terms of both time and money. The development and validation of brief measures of HAI are important to encourage the inclusion of these measures in larger surveys. This paper describes the psychometric properties of two brief attachment measures used in the 2014 Panel Study of Income Dynamics (PSID) Child Development Supplement (CDS), the first population-representative study of child development in the United States that includes HAI items. We use two measures derived from the 36 item CENSHARE scale. For children aged 8-17, a 6-item measure was included; for the primary caregiver, a 3-item measure was included. The results suggest that such brief measures of attachment to pets are psychometrically valid and may be a practical method of measuring attachment in larger surveys using a smaller number of survey items. We encourage HAI researchers to work with other ongoing surveys to incorporate these and comparable measures.